Decision Support System based on Industry 5.0 in Artificial Intelligence - Srinivasan, S.; Hema, D. Deva; Singaram, Balaji; Praveena, D.; Mohan, K. B. Kishore; Preetha, M. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The term "Industry 5.0" was created to address personalized production and the empowerment of humans in manufacturing processes, as Industry 4.0 was unable to meet the increasing need for customization. There are differing opinions about what Industry 5.0 is and what comprises the reconciliation of humans and robots from the term's inception. A new "proof of concept" for enhanced Process Mining is to be adopted to automate decision-making, optimize machine settings, and conduct maintenance interventions to provide a novel method for modeling production management in industry. Both supervised and unsupervised artificial intelligence techniques are incorporated into the PM model's complex electrical sensing and actuation subsystems. These systems facilitate intelligent decision-making by suggesting theoretical process workflows that are powered by a Decision Support System (DSS) engine. By solving these identified obstacles, future researchers may enhance the decision assistance systems. Every decision support system is subjected to a methodical analysis. An extensive assessment is carried out considering many factors such as compatibility, expandability, ease of use, and so on. Future issues are identified and outlined based on the evaluation's findings, which also reveal development trends and offer suggestions for future research directions.